POST-COVID-19 PANDEMIC RECOVERY OF HOUSEHOLD WELFARE - Marsus, Soffan; Ashari, Hasan; Nugrahanti, Trinandari Prasetya (Fakultas Ekonomi dan Bisnis, UNTAN, 2024)
This study aims to investigate the post-COVID-19 pandemic recovery on household welfare in the Greater Jakarta area a result of the government